Macular surgery - Quiroz-Mercado, Hugo.; Kerrison, John B. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)
"The second edition of Macular Surgery has been completely rewritten to reflect diagnostic and therapeutic point of view. Macular surgery has been most dramatically impacted by the development of smaller instrumentation allowing surgery to be performed more rapidly and with less morbidity. The continued advancement of ocular coherence tomography has allowed the surgeon greater insight into diseases of the vitreo-macular interface including macular hole, epiretinal membrane, and vitreo-macular traction"--Provided by publisher.